Predicting Phrenic Nerve Palsy in Patients Undergoing Atrial Fibrillation Ablation With the Cryoballoon—Does Sex Matter? - Pott, Alexander; Wirth, Hagen; Teumer, Yannick; Weinmann, Karolina; Baumhardt, Michael; Schweizer, Christiane; Markovic, Sinisa; Buckert, Dominik; Bothner, Carlo; Rottbauer, Wolfgang; Dahme, Tillman (Frontiers in Cardiovascular Medicine, 2021)
Background: Phrenicus nerve palsy (PNP) is a typical complication during pulmonary vein isolation (PVI) using the cryoballoon with the ominous potential to counteract the clinical benefit of restored sinus rhythm. According to current evidence incidence of PNP is about 5–10% of patients undergoing Cryo-PVI and is more frequent during ablation of the RSPV compared to the RIPV. However, information on patient specific characteristics predicting PNP and long-term outcome of patients suffering from this adverse event is sparse. Aim of the Study: To evaluate procedural and clinical characteristics of AF patients with PNP during cryoballoon PVI compared to patients without PNP. Methods and Results: Between 2013 and 2019 we included 632 consecutive AF patients undergoing PVI with the cryoballoon in our study. 84/632 (13.3%) patients experienced a total number of 89 PNP during the ablation procedure. 75/89 (84%) cryothermal induced PNP recovered until the end of the procedure (transient PNP, tPNP), whereas 14/89 (16%) PNP hold beyond the end of the procedure (non-transient PNP, ntPNP). Using multivariate logistic regression, we found that sex and BMI are strong and independent predictors of cryothermal induced non-transient PNP during cryoballoon PVI with an odds ratio of 3.9 (CI: 95%, 1.1–14.8, p = 0.04) for female gender. Interestingly, all patients (14/14, 100%) with a non-transient PNP experienced complete PNP resolution after a mean recovery time of 68 ± 79 days. Conclusion: Our data indicate for the first time, that female sex and lower BMI are independent predictors for non-transient PNP caused by cryoballoon PVI. Fortunately, during follow up all PNP patients resolved completely with a median recovery time of 35 days.